Critical aspects of yellow fever control in Brazil - Tauil, Pedro Luiz (Revista de Saúde Pública, 2010)
This paper presents epidemiological and control characteristics of yellow fever in Brazil, taking its wild and urban transmission cycles into consideration. No urban cases have been reported in Brazil since 1942, but urban yellow fever cases were reported in Paraguay in 2008, after more than 50 years without registered cases in the Americas. The two main objectives of yellow fever control programs in Brazil are to reduce the number of wild cases and to maintain zero incidence of urban cases. Although there is a consensus regarding control measures that should be applied in areas endemic for the wild form, this is not so in relation to areas infested by Aedes aegypti. The arguments for and against expansion of the vaccination area are discussed. Environmental and entomological studies are needed so that areas receptive to wild-type transmission can be recognized, even if they have been silent for many years.